Visual affordances and object selection - Riddoch, M; Humphreys, G; Edwards, MG (2000)
Neuropsychological evidence indicates that actions may be evoked directly by visually presented objects. Such actions are affected by learned association with objects and by congruency between the parts of objects and (1) the goal state of the actor; and (2) the effectors used for action (" affordance"). Patients who are unable to conform to a task rule and who show aspects of frontal lobe utilization behavior can be shown to make inappropriate actions in response to objects, actions that are influenced both by object-action associations and by affordances, although such patients remain able to appropriately select objects for action. Thus the processes involved in selecting a visual object for action appear to precede and to be separated from those involved in selecting a given hand with which to respond (according to a predefined task rule). Further data suggest that once an object is selected for a manual reaching action, other objects in the trajectory of the reach compete for the action. This secondary stage of competition may be useful for navigating between objects in neurologically intact individuals, but can lead to difficulties for patients with problems in action selection.